Competition load and stress in sports: a preliminary study in biathlon - Manfredini, F.; Manfredini, R.; Carrabre, J. E.; Litmanen, H.; Zhukovskaja, L.; dal Follo, D.; Haberstroh, J. (International Journal of Sports Medicine, 2002)
International sports calendars are being increasingly filled with competitive events and fatiguing travel, at the risk of overloading the athletes involved. The Medical Committee of the International Biathlon Union, in order to check for any significant changes, analysed seven recent competitive seasons, calculating the number of races and total and daily numbers of racing kilometers for each season. A theoretical model for stress was subsequently developed, based on identification and quantification of favourable and unfavourable factors, with establishment of average and maximal stress scores for each season. A questionnaire was distributed to athletes to collect data about daily stress levels, and the correspondence between the theoretical model and the athletes' responses was determined. This analysis demonstrates that the biathlon has become more demanding for those athletes in the racing circuit, with significant increases in number of races, total and daily numbers of kilometers raced, and average stress scores for athletes of both sexes. The self-reported daily stress levels for some athletes show an interesting correspondence with the theoretical stress model. If such correspondence is confirmed, this model might constitute an instrument with which international sports federations, considering the concentration of races, related travel and recovery times, could plan sustainable competitive calendars.